Distinct in vivo roles of secreted APP ectodomain variants APPsα and APPsβ in regulation of spine density, synaptic plasticity, and cognition - Richter, Max; Bold, Charlotte; Klein, Susanne; Han, Kang; Weyer, Sascha W.; Müller, Ulrike C. (The EMBO journal, 2018)
Increasing evidence suggests that synaptic functions of the amyloid precursor protein (APP), which is key to Alzheimer pathogenesis, may be carried out by its secreted ectodomain (APPs). The specific roles of APPsα and APPsβ fragments, generated by non-amyloidogenic or amyloidogenic APP processing, respectively, remain however unclear. Here, we expressed APPsα or APPsβ in the adult brain of conditional double knockout mice (cDKO) lacking APP and the related APLP2. APPsα efficiently rescued deficits in spine density, synaptic plasticity (LTP and PPF), and spatial reference memory of cDKO mice. In contrast, APPsβ failed to show any detectable effects on synaptic plasticity and spine density. The C-terminal 16 amino acids of APPsα (lacking in APPsβ) proved sufficient to facilitate LTP in a mechanism that depends on functional nicotinic α7-nAChRs. Further, APPsα showed high-affinity, allosteric potentiation of heterologously expressed α7-nAChRs in oocytes. Collectively, we identified α7-nAChRs as a crucial physiological receptor specific for APPsα and show distinct in vivo roles for APPsα versus APPsβ. This implies that reduced levels of APPsα that might occur during Alzheimer pathogenesis cannot be compensated by APPsβ.
Gesehen am 26.04.2018